A Comparative Study of Resistivity Sounding Curves from Two Drainage Areas of Kafanchan, Kaduna State - Akwuba, Godwin Kingsley (Obafemi Awolowo University, 2014)
A comparative analysis of resistivity sounding curves obtained from two drainage areas near Kafanchan, Kaduna state, underlain by rocks of the Precambrian basement complex of Nigeria, was carried out. A small part of one of the areas is occupied by the newer basalt. The resistivity investigation was done by the ACME Drillers Limited, Lagos under the auspices of Kaduna State Water Board, Kaduna.